Effects of food processing on the lipid nutritional quality of commercially important fish and shellfish - Karsoon Tan; Lim, Leong Seng; Ya Peng; Cheong, Kit Leong (Elsevier Ltd., 2023)
Fish and shellfish are important sources of high quality lipids, especially omega-3 long-chain polyunsaturated fatty acids. In most countries, seafood is eaten cooked to eliminate any potential parasites and pathogens. In addition, cold storage plays an important role in extending the shelf life of seafood. However, both cooking and storage processes can cause alterations in the lipid content and fatty acid profile of fish and shellfish. Although the lipid nutritional quality of fish and shellfish have recently been reviewed, these reviews mainly focus on raw seafood, and information on the impact of food processing on the lipid nutritional quality of fish and shellfish still lacks coherence. Therefore, this study was carried out to provides a critical reviews on the effects of food processing, especially cooking and cold storge, on the lipid nutritional quality of fish and shellfish. Overall, from the perspective of lipid nutritional quality, baking and steaming are the most recommended cooking methods for fish and shellfish, respectively, while it is strongly not recommended to fry seafood with margarine. For cold storage, 3 days and 2 weeks are the most recommended storage periods for refrigeration and frozen storage, respectively. This article can provides consumers with useful information to choose food preparation and storage methods based on their personal interest in specific lipid nutritional quality indicators.